THE EFFECT OF VESTIBULA STIMULATION TRAINING ON GAIT ABILITY FOR CHRONIC STROKE PATIENT - Kim, Myeong-Jun; Kim, Tae-Ho; Park, Jin (International Journal of Psychosocial Rehabilitation, 2020)
Stroke patients have significantly reduced their functions of vestibular sensory and proprioception. thus, excessive reliance on vision is used as a strategy. The purpose of this study was to examine differences according to method of exercise in gait ability for stroke patient.The study subjects included 30 patients with stroke, who were divided into eyehead coordination vestibular training group (n1=15) and unstable base balance training(n2=15) groups. Groups underwent vestibula stimulus training five times per week, 20 min per session, for six weeks. To examine gait ability, Gait-checker was used. And experimental results were obtained by comparing Step length, step time, Timed up and go test were significantly increased in the vestibula stimulus training group (p